FSR 1776: A new globular cluster in the Galactic bulge? - Dias, B. (2022)
Context. Recent near-IR surveys have uncovered a plethora of new globular cluster (GC) candidates towards the Milky Way bulge. These new candidates need to be confirmed as real GCs and properly characterised. Aims. We investigate the physical nature of FSR 1776, a very interesting star cluster projected towards the Galactic bulge. This object was originally classified as an intermediate-age open cluster, and has recently been re-discovered independently and classified as a GC candidate (Minni 23). Firstly, our aim is to confirm its GC nature; secondly, we determine its physical parameters. Methods. The confirmation of the cluster existence is checked using the radial velocity (RV) distribution of a MUSE data cube centred at FSR 1776. The cluster parameters are derived from isochrone fitting to the RV-cleaned colour-magnitude diagrams (CMDs) from visible and near-IR photometry taken from VVV, 2MASS, DECAPS, and Gaia all together. Results. The predicted RV distribution for the FSR 1776 coordinates, considering only contributions from the bulge and disc field stars, is not enough to explain the observed MUSE RV distribution. The extra population (12% of the sample) is FSR 1776 with an average RV of -103.7  ±  0.4  km  s-1. The CMDs reveal that it is 10 ± 1 Gyr metal-rich population with [Fe/H]phot  ≈  +0.2  ±  0.2, [Fe/H]spec  =  +0.02  ±  0.01(σ  =  0.14 dex), located at the bulge distance of 7.24 ± 0.5 kpc with AV ≈ 1.1 mag. The mean cluster proper motions are (⟨ μα⟩,⟨ μδ⟩) = (-2.3  ±  1.1,  -2.6  ±  0.8) mas  yr-1. Conclusions. FSR 1776 is an old GC located in the Galactic bulge with a super-solar metallicity, among the highest for a Galactic GC. This is consistent with predictions for the age-metallicity relation of the bulge, being FSR 1776 the probable missing link between typical GCs and the metal-rich bulge field. High-resolution spectroscopy of a larger field of view and deeper CMDs are now required for a full characterisation.